INTERMITTENT HYPOBARIC HYPOXIC STIMULATION IN TREATMENT OF CHILDREN WITH BRONCHIAL ASTHMA AT THE PERIOD OF REHABILITATION - G.D. Alemanova (Union of pediatricians of Russia, 2009)
Bronchial asthma is one of the widespread chronic diseases of lungs. Immune mechanisms of disorder are one of the causes which lead to pathologic changes in lungs. The aim: to determine the clinical and immunologic effectiveness of pressure adaptation to the periodical hypobaric hypoxic stimulation of treatment of children with bronchial asthma of prepubertal and pubertal periods. In the present work there were observed the clinical and immunologic parameters of 129 children with the verified atopic bronchial asthma of different degree at the remission period before and after the course of pressure adaptation to the periodical hypobaric hypoxic stimulation in conditions of the medical hypobaric pressure chamber with many seats «Ural'1». Clinic effectiveness of hypobaric hypoxic stimulation revealed in continuation of remissions and diminishing of total numerical score of asthma degree. The positive dynamic indexes of cytokine profile was observed. It revealed in reduction of IL 1_, IL 4, IL 5, IL 18 levels and stimulated production of IFN - in blood serum. The course of hypobaric hypoxic stimulation has the positive impact on the named indexes of the patients with bronchial asthma and its intensity depends on the degree of disease and of the age of the child' patient. Thus the use of pressure adaptation to the periodical hypobaric hypoxic stimulation in treatment of children's with bronchial asthma led to the immunologic positive dynamics, especially of the children of prepubertal period. Determination of the immunologic indexes and the level of the cytokines can be used as the additional tests for the evaluation of the effectiveness of pressure adaptation to the periodical hypobaric hypoxic stimulation of children.Key words: bronchial asthma, periodical hypobaric hypoxic stimulation, cytokines, children.